Enhancing the Efficiency of Customer Data Search in Pamsimas Using QR Code Technology - Wildan Razzaq Pratama; Yuli Purwati; Ali Nur Ikhsan (INOVTEK Polbeng - Seri Informatika, 2024)
Pamsimas is a government program aimed at providing clean water access for rural communities, including Desa Melung, which manages these services through BUMDes Alam Lestari. However, the customer data retrieval process on BUMDes's website is still manual, impacting both efficiency and accuracy. This study aims to improve data retrieval efficiency by implementing QR code technology. Each customer is assigned a unique code that can be scanned to quickly access their information. Testing results indicate that the QR code implementation reduced data retrieval time by 65% and lowered recording errors by 45%, thus expediting service processes and enhancing customer satisfaction. These findings suggest that QR codes are effective in enhancing operational efficiency and data management accuracy in public service sectors.